Design and feasibility evaluation of low-cost 3D printing of Horn Antennas - Gao, Ming (Department of Electrical Engineering, 2020)
This dissertation investigates advances in additive manufacturing (AM) technology to determine the feasibility of low-cost 3D printing of horn antennas. Relevant antenna theory and current 3D printing technologies are reviewed and a literature review is conducted looking specifically at microwave and RF devices that have been fabricated using 3D printing technologies. The literature indicates that the fabrication of antennas using AM and metallisation techniques is realisable. One of the objectives of this study has been to design, fabricate and test the performance of lowcost 3D printed antennas to determine their feasibility. To achieve this, a commercial X-band pyramidal horn has been replicated using the microwave simulation package FEKO. The X-band horn has been fabricated using an FDM-based 3D printer and metallised using conductive paint. Ku-band pyramidal and conical horns have also been designed and 3D printed using the same method and have been metallised using both conductive paint and electroplating. The fabricated horns have been measured and tested in an anechoic chamber with the measured results analysed. The fabricated X-band pyramidal horn achieved a gain of 9.2 dBi with an input reflection coefficient of −11.9 dB at a centre frequency of 10 GHz. This is in agreement with the measured gain and reflection coefficient of the X-band commercial horn. The Ku-band pyramidal horns that have been metallised using conductive paint and copper plating achieved gains of 17.5 dBi and 17.7 dBi respectively, measured at a centre frequency of 15 GHz. The input reflection coefficients for the painted Ku-band pyramidal horns are measured as −24.2 dB while the copper plated horns are measured as −23.3 dB. The second set of Ku-band conical horn antennas designed have also been metallised using conductive paint and copper plating. These two antennas achieved gains of 12.0 dBi and 16.6 dBi respectively at a centre frequency of 15 GHz. The input reflection coefficient for the painted Kuband conical horn is −15.2 dB while the plated version has a reflection coefficient of −18.3 dB. The total cost of fabricating and testing each antenna amounted to approximately ZAR 475 per antenna, an order of magnitude lower than the price of a traditional cast or milled antenna. The method of fabrication demonstrated in this report is relatively fast and inexpensive while producing favourable results. As such, this method is highly suited for rapid prototyping and development of more advanced antenna designs.